Jubileumskonsert : Norrbottens kammarorkester firar 30 år (2021)
Norrbottens Kammarorkester celebrates it's 30th anniversary as well as the northern cities of Torneå, Luleå and Piteå and their 400th anniversaries with four commissions and world premieres together with music by Stenhammar, Strauss and Tchaikovsky. Validerad;2021;Nivå 1;2021-12-16 (svasva)